2021
DOI: 10.1001/jamaophthalmol.2021.1660
|View full text |Cite|
|
Sign up to set email alerts
|

Defining Nonadherence and Nonpersistence to Anti–Vascular Endothelial Growth Factor Therapies in Neovascular Age-Related Macular Degeneration

Abstract: IMPORTANCEPoor adherence or persistence to treatment can be a barrier to optimizing clinical practice (real-world) outcomes to intravitreal injection therapy in patients with neovascular age-related macular degeneration (nAMD). Currently, there is a lack of consensus on the definition and classification of adherence specific to this context. OBJECTIVE To describe the development and validation of terminology on patient nonadherence and nonpersistence to anti-vascular endothelial growth factor therapy.DESIGN, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…For instance, in recent work, a definition of non-adherence and non-persistence was developed by a group of retinal experts, who classified reasons for treatment non-adherence/non-persistence in nAMD patients requiring IVT anti-VEGF therapy. 31 This could provide a framework for future assessments in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in recent work, a definition of non-adherence and non-persistence was developed by a group of retinal experts, who classified reasons for treatment non-adherence/non-persistence in nAMD patients requiring IVT anti-VEGF therapy. 31 This could provide a framework for future assessments in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was the definition of nonpersistence as nonattendance to any treatment or monitoring visit for 6 months. This was partly owed to long treatment intervals of up to 16 weeks; thus, a cut-off after 4 months would be too short [ 8 ]. To address all these challenges, future investigations could determine their nonattendance cut-off depending on the treatment protocol and/or the patients’ individual treatment interval.…”
Section: Discussionmentioning
confidence: 99%
“…The functional and anatomical outcomes of eyes that were persistent to intravitreal aflibercept therapy (persistent group) were compared to the outcomes of eyes that were nonpersistent to therapy for at least 6 months during their individual observation period (the nonpersistent group). As suggested by Okada et al, we defined nonpersistence as not attending any scheduled treatment or monitoring visit for any reasons for at least 6 months within the observational period [ 8 ]. Patients who were scheduled beyond 6 months for the follow-up were not considered as nonpersistent.…”
Section: Methodsmentioning
confidence: 99%
“…Randomized controlled trials (RCT) showed that individualized PRN and T&E are not inferior to fixed treatment regimens but mitigate treatment burden for the patient 8 – 10 . However, the average number of intravitreal injections applied by PRN or T&E in real-world setting is consistently lower than in RCTs due to multifactorial reasons including the patient, physician, treatment center set up and logistical factors 11 15 . Concurrently, VA gains observed in real-world settings stay below those observed in RCT.…”
Section: Introductionmentioning
confidence: 93%